2006
DOI: 10.1192/pb.30.10.376
|View full text |Cite
|
Sign up to set email alerts
|

‘Do not resuscitate’ decisions in continuing care psychiatric patients: what influences decisions?

Abstract: Aims and MethodWe evaluated the various aspects of ‘do not resuscitate’ (DNR) decisions taken for psychiatric continuing care patients within NHS Ayrshire and Arran. Records were reviewed and nursing staff were asked their opinions about DNR orders in general and the way these were implemented on their wards.ResultsThere were 35 DNR orders among 88 continuing care patients in mental health wards for older adults. There were no DNR orders for the 25 continuing care patients in general adult psychiatry wards. Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…79,84,85 Sometimes there were less than 24 hours before death, 84,85 with many emergency teams having to decide moments before death whether or not there was a DNACPR order already in place. 66,76,86,90,91 In one Scottish study, 87 consultants on general adult wards and those in old-age psychiatry differed in their opinions about whether or not a DNACPR order should be issued at all: some would discuss this with the family in cases where the patient may live for many more years and others would raise it only if the patient was clearly at the end of his or her life. There were indications that the longer the duration of the stay in hospital the more DNACPR orders were documented, 16 sometimes after a prolonged stay and aggressive therapeutic measures.…”
Section: Timingmentioning
confidence: 99%
See 4 more Smart Citations
“…79,84,85 Sometimes there were less than 24 hours before death, 84,85 with many emergency teams having to decide moments before death whether or not there was a DNACPR order already in place. 66,76,86,90,91 In one Scottish study, 87 consultants on general adult wards and those in old-age psychiatry differed in their opinions about whether or not a DNACPR order should be issued at all: some would discuss this with the family in cases where the patient may live for many more years and others would raise it only if the patient was clearly at the end of his or her life. There were indications that the longer the duration of the stay in hospital the more DNACPR orders were documented, 16 sometimes after a prolonged stay and aggressive therapeutic measures.…”
Section: Timingmentioning
confidence: 99%
“…87 There were more DNACPR orders written in acute wards than in planned admissions such as surgical wards. 70 This is illustrated by one study 16 which found more DNACPR orders in acute admissions (n = 99/119) than in planned admissions (n = 20/119; p < 0.05); the most frequently written DNACPR orders came from internal medicine and pulmonology, with fewer from cardiology, thoracic surgery and neurosurgery wards.…”
Section: Settingmentioning
confidence: 99%
See 3 more Smart Citations